ENSINO E TECNOLOGIAS NO ENSINO FUNDAMENTAL: INVESTIGAÇÃO DE PRÁTICAS DE ALFABETIZAÇÃO EM ESCOLA DE NOVA PALMA-RS NO CONTEXTO DA PANDEMIA - Pigatto, Fernanda Rodrigues (2021)
In view of the COVID-19 pandemic in 2020, schools have reorganized their calendars, school days have been rethought and, in many cases, teachers had to conduct classes and teaching practices through virtual means or other viable alternatives . Given this emergency situation, education at all levels was affected, above all, elementary education for children in the literacy phase. In this dissertation research project, the general objective is to analyze what changes can be seen in the literacy practices of teachers at a municipal school in Nova Palma, RS, in the context of the coronavirus pandemic. As specific objectives, it is intended to: Detect changes in literacy teaching practices in the initial grades of the selected school; To verify which means and materials were used by teachers to continue teaching literacy practices; Check what guidelines were given, by schools or municipal bodies, to teachers, on pedagogical practices; To raise, from the teachers' reports, difficulties and positive aspects found in this pandemic teaching context. This is a qualitative research, with a case study method, and the research participants are teachers in the early years of elementary school at the selected school. The results show that, for early childhood education and literacy, many factors make this situation more complex than working with other grades, as children need more intense supervision and monitoring, as well as daily stimuli.